A UTILIZAÇÃO DA INTELIGÊNCIA ARTIFICIAL PARA A GESTÃO DE PRODUTIVIDADE: ENTRE A EFICIÊNCIA EMPRESARIAL E A PROTEÇÃO DOS DIREITOS FUNDAMENTAIS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The growing use of artificial intelligence in business practices has profoundly transformed the way companies organize themselves, assess, and control the productivity of their employees. In this regard, algorithmic tools capable of collecting, processing, and analyzing large volumes of data enable employers to measure both individual and collective performance, thereby promoting efficiency and the optimization of resources. However, this development does not occur without controversy. The use of artificial intelligence as an instrument of monitoring and productivity management raises questions not only about its effects but also about its legal and ethical limits, particularly with respect to workers’ fundamental rights—such as privacy, dignity, freedom, and equality. These constitutional guarantees may be undermined by constant surveillance and by automated decision-making processes, which often elude transparency and human oversight. In this context, Labor Law embraces technological advances that enable companies to become more competitive, but how can we ensure that such innovations do not result in abusive practices or new forms of legal precariousness? A problem arises: how to reconcile the use of artificial intelligence in productivity management with the protection of employees' fundamental rights? This study seeks to reflect on this tension, investigating the risks and the potential for a link between corporate efficiency and legal protection in light of the protection of workers' fundamental rights.